2015
DOI: 10.1111/andr.12063
|View full text |Cite
|
Sign up to set email alerts
|

Rare double sex and mab-3-related transcription factor 1 regulatory variants in severe spermatogenic failure

Abstract: The DMRT1 (doublesex and mab-3 related transcription factor 1) gene has long been linked to sex-determining pathways across vertebrates and is known to play an essential role in gonadal development and maintenance of spermatogenesis in mice. In humans, the genomic region harboring the DMRT gene cluster has been implicated in disorders of sex development and recently DMRT1 deletions were shown to be associated with non-obstructive azoospermia (NOA). In this work we have employed different methods to screen a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(57 reference statements)
1
11
1
3
Order By: Relevance
“…Thus, simultaneous loss of function of DMRT1 and DMRT3 (or DMRT1, DMRT2, and DMRT3) in those patients could have more severe effect on gonadal development than single gene knockout. Accordingly, small deletions that affect only several exons of the DMRT1 gene or regulatory variants of DMRT1 are found in patients with milder gonadal dysfunction, such as male infertility [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, simultaneous loss of function of DMRT1 and DMRT3 (or DMRT1, DMRT2, and DMRT3) in those patients could have more severe effect on gonadal development than single gene knockout. Accordingly, small deletions that affect only several exons of the DMRT1 gene or regulatory variants of DMRT1 are found in patients with milder gonadal dysfunction, such as male infertility [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Its haplo-insufficiency causes a block in the elongation stage of spermiogenesis in mice, leading to asynchronous spermatid maturation (Yan et al, 2004). Deletions and missense mutations in DMRT1 are associated with a wide spectrum of phenotypes, from XY gonadal dysgenesis to disorders of spermatogenesis such as cryptozoospermia, SCO and meiotic arrest (Tewes et al, 2014;Lima et al, 2015;T€ uttelmann et al, 2018). The same variant we found, c.671A>G, has already been reported in two patients with SCO (Tewes et al, 2014), whereas missense and splicing variants in KLHL10 have only been associated with oligozoospermia in humans (Yatsenko et al, 2006;Miyamoto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in 2015, the Lopes' group identified three additional noncoding variants located in regulatory regions of DMRT1, by analysing a Portuguese study cohort of 155 NOA and 376 controls (75 normozoospermic and 301 with self-reported fatherhood) using a multiplex ligation probe assay and Sanger sequencing [112]. One of them, located in the promoter region, showed clear evidence of a key regulatory role in Dmrt1 repression.…”
Section: Dmrt1mentioning
confidence: 99%